Pulmonary Infarction: An Often Unrecognized Clinical Entity - Miniati, Massimo (Seminars in Thrombosis and Hemostasis, 2016)
Pulmonary infarction occurs in nearly one-third of the patients with acute pulmonary embolism. Infarcts are still often mistaken for pneumonia or lung cancer because of the deeply rooted belief that they ought to be triangular in shape. In reality, the apical portion of an embolized region is spared from infarction thanks to sufficient collateral blood flow. Infarcts are always arranged peripherally along the surface of the visceral pleura (costal, diaphragmatic, mediastinal, or interlobar). Their free margin is sharp and convex toward the hilum, casting a semicircular or cushion-like density on chest radiography or computed tomography (CT). Focal areas of hyperlucency within the infarction are often seen on CT. Clinical presentation is nonspecific. Pleuritic chest pain, either isolated or in combination with abrupt dyspnea, is the most frequent presenting symptom, whereas hemoptysis is much rarer. Recent data indicate that younger age, increasing body height, and active cigarette smoking are independent predictors of infarction in the setting of acute pulmonary embolism. Correct recognition of pulmonary infarction is fundamental because pleural-based consolidations suggestive of infarction may be the first manifestation of pulmonary embolism.
Keywords: pulmonary infarction; morphology; risk factors; diagnosis